Deep learning-assisted (automatic) diagnosis of glaucoma using a smartphone. Issue 4 (14th July 2021) - Nakahara, Kenichi; Asaoka, Ryo; Tanito, Masaki; Shibata, Naoto; Mitsuhashi, Keita; Fujino, Yuri; Matsuura, Masato; Inoue, Tatsuya; Azuma, Keiko; Obata, Ryo; Murata, Hiroshi
Abstract : Background/aims: To validate a deep learning algorithm to diagnose glaucoma from fundus photography obtained with a smartphone. Methods: A training dataset consisting of 1364 colour fundus photographs with glaucomatous indications and 1768 colour fundus photographs without glaucomatous features was obtained using an ordinary fundus camera. The testing dataset consisted of 73 eyes of 73 patients with glaucoma and 89 eyes of 89 normative subjects. In the testing dataset, fundus photographs were acquired using an ordinary fundus camera and a smartphone. A deep learning algorithm was developed to diagnose glaucoma using a training dataset. The trained neural network was evaluated by prediction result of the diagnostic of glaucoma or normal over the test datasets, using images from both an ordinary fundus camera and a smartphone. Diagnostic accuracy was assessed using the area under the receiver operating characteristic curve (AROC). Results: The AROC with a fundus camera was 98.9% and 84.2% with a smartphone. When validated only in eyes with advanced glaucoma (mean deviation value < −12 dB, N=26), the AROC with a fundus camera was 99.3% and 90.0% with a smartphone. There were significant differences between these AROC values using different cameras. Conclusion: The usefulness of a deep learning algorithm to automatically screen for glaucoma from smartphone-based fundus photographs was validated. The algorithm had a considerable high diagnostic ability, particularly in eyes with advanced glaucoma.